The Relationship Between Entrepreneurial Activity (In Switzerland) Against Motivational Index, Innovation, Business Service Sector - Huseynzade, Abbas (Digital Repository of Theses - SSBM Geneva, 2025)
This research paper investigates the relationship between entrepreneurial activity in Switzerland and three variables: the Motivational Index, Innovation, and the Business Service Sector. The aim of the study is to investigate how motivational index, innovation and business service sector influences individuals in Switzerland to intend to start an entrepreneurial project or to actually engage in starting a new business. Using data from the Global Entrepreneurship Monitor (GEM), this research employs a quantitative approach through multi-linear regression models to assess the significance of each variable on entrepreneurial activity and intention. The findings reveal that among the variables studied, only the Motivational Index has a significant influence on entrepreneurial activity. Furthermore, the results reveal an insignificant impact on Entrepreneurial Intention from all the included variables. The results support individual-level theories such as the Theory of Planned Behavior, while challenging institutional theories like the Entrepreneurial Ecosystem model. Recommendations are made for Swiss policymakers to prioritize motivationenhancing policies and raise awareness about innovation and support infrastructure. This research contributes to theory, practice, and policymaking by identifying the key drivers that stimulate entrepreneurship in Switzerland.